The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fmicb.2023.1193990
|View full text |Cite
|
Sign up to set email alerts
|

Soil chemistry, metabarcoding, and metabolome analyses reveal that a sugarcane—Dictyophora indusiata intercropping system can enhance soil health by reducing soil nitrogen loss

Abstract: IntroductionGreater amounts of fertilizer are applied every year to meet the growing demand for food. Sugarcane is one of the important food sources for human beings.MethodsHere, we evaluated the effects of a sugarcane—Dictyophora indusiata (DI) intercropping system on soil health by conducting an experiment with three different treatments: (1) bagasse application (BAS process), (2) bagasse + DI (DIS process), and (3) the control (CK). We then analyzed soil chemistry, the diversity of soil bacteria and fungi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
(73 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, in the sugarcane root of DI, the Bacillus genus was associated with the same abundance as D. indusiata (Phallaceae) ( Figures 3E, F ). Interestingly, based on my preliminary research, it was also found that the DI treatment has the ability to reduce soil fungal diversity, which aligns with the observed decreasing trend in endophytic fungal diversity in this study ( Duan et al., 2023a ). This indicates that the cultivation of D. indusiata may invasive and symbiotic growth with sugarcane root, which in turn may regulate the metabolism of sugarcane roots and ultimately impact sugarcane growth.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, in the sugarcane root of DI, the Bacillus genus was associated with the same abundance as D. indusiata (Phallaceae) ( Figures 3E, F ). Interestingly, based on my preliminary research, it was also found that the DI treatment has the ability to reduce soil fungal diversity, which aligns with the observed decreasing trend in endophytic fungal diversity in this study ( Duan et al., 2023a ). This indicates that the cultivation of D. indusiata may invasive and symbiotic growth with sugarcane root, which in turn may regulate the metabolism of sugarcane roots and ultimately impact sugarcane growth.…”
Section: Discussionsupporting
confidence: 88%
“…In this study’s intercropping system, D. indusiata significantly improved the metabolism of sugarcane roots through root symbiosis. Studies have found that the D. indusiata fruiting bodies synthesize IAA ( Duan et al., 2023b ), and D. indusiata improves soil metabolism, accumulating carbohydrate metabolites ( Duan et al., 2023a ). These earlier reports suggested that D. indusiata promotes plant growth metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil non-targeted metabolomics can be used to characterize the differential activity of microbial communities ( Abram, 2015 ) and reflect the interaction between the microbial genome and the environment ( Tang, 2011 ), providing a novel approach for assessing soil health. For example, alterations in soil carbohydrate metabolite abundance are influenced by factors such as soil organic matter content and microbial activity ( Duan et al, 2023 ). Therefore, soil metabolomics is valuable for assessing the impact on soil quality and microbial function ( Withers et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the growth of Leucocalocybe mongolica mycelium in soil in a fairy ring ecosystem has been shown to increase soil nutrient abundance ( Duan et al, 2022a ); this can in turn enhance plant growth, increase the abundance of flavonoid metabolites, and promote hormone synthesis ( Duan et al, 2022b ). The cultivation of Dictyophora indusiata inhibits the activity of soil urease, which reduces the environmental loss of soil N ( Duan et al, 2023a ). Therefore, the cultivation of macrofungi (mushrooms) has a major effect on soil ecology.…”
Section: Introductionmentioning
confidence: 99%